Association of serum hepatoma‐derived growth factor levels with disease activity in rheumatoid arthritis: A pilot study. Issue 6 (2nd May 2022) - Ahn, Sung Soo; Kim, Hye Min; Park, Younhee
Abstract: Background: Hepatoma‐derived growth factor (HDGF) is reported to play an important role in tumorigenesis and cancer progression. However, growing evidence indicates its participation in immune system activation. This study analyzed the relationship among serum HDGF levels, disease activity, and laboratory markers in patients with rheumatoid arthritis (RA). Methods: Blood samples from 165 patients with RA, 42 with osteoarthritis (OA), and 28 healthy controls, were used to evaluate the serum HDGF levels. Correlations of serum HDGF levels with age, 28‐joint count disease activity score (DAS28), and laboratory findings were assessed by Pearson correlation and receiver operator characteristic (ROC) curve analyses to obtain HDGF optimal cutoffs according to the disease status. Immunohistochemical staining was performed on the knee synovial tissue samples from patients with RA and OA ( n  = 10 each) to investigate HDGF joint expression. Results: Serum HDGF levels were significantly correlated with DAS28 erythrocyte sedimentation rate ( r  = 0.412, p  < 0.001) and C‐reactive protein values ( r  = 0.376, p  < 0.001). The optimal cutoffs of serum HDGF levels from the ROC analysis were 5.79 and 5.14 for the differentiation of active/inactive disease and remission/non‐remission, respectively. The ideal cutoff of serum HDGF levels to differentiate RA and OA was determined as 5.47. Serial serum HDGF level analyses in 21 patients with RA revealed that serum HDGF levels significantly decreased after improvement in disease activity ( p  = 0.046). HDGF expression was not observed in the synovial tissues of the patients with RA and OA. Conclusion: Serum HDGF level could be a potential laboratory biomarker for the severity of RA. Abstract : Serum hepatoma‐derived growth factor (HDGF) levels were significantly correlated with disease activity in patients with rheumatoid arthritis (RA), which decreased after the improvement of disease activity. In addition, serum HDGF level was significantly higher in patients with active RA than in those with inactive RA, osteoarthritis, and healthy controls. Our results suggest serum HDGF level could be a potential laboratory biomarker for the severity of RA.